Rynki finansowe jako determinanta konkurencyjności regionów Unii Europejskiej - Borowiec, Jan (Financial markets as a factor of competitiveness of the region, 2006)
Financial markets are principal factors of regional competitiveness. It is a consequence of their role in mobilization of saving, allocation of capital between regions and sectors ofeconomy, and risk diversification. Effectiveness in financial markets depends on many factors, including the level of financial development, financial structure, and market regulation. There is a positive relation between financial development and economic growth, especially strong in initial stage of economic development. Therefore financial markets promote the development and competitiveness of regions whose development is lagging behind.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1129, s. 392-407